2016
DOI: 10.2147/ijn.s105575
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent cytotoxicity of Fe<sub>3</sub>O<sub>4</sub> nanoparticles induced by biphasic regulation of oxidative stress in different human hepatoma cells

Abstract: The application of Fe3O4 nanoparticles (NPs) has made great progress in the diagnosis of disease and in the drug delivery system for cancer therapy, but the relative mechanisms of potential toxicity induced by Fe3O4 have not kept pace with its development in the application, which has hampered its further clinical application. In this article, we used two kinds of human hepatoma cell lines, SK-Hep-1 and Hep3B, to investigate the cytotoxic effects and the involved mechanisms of small Fe3O4 NPs with different di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 37 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…The selected literature was classified into four main groups:Methods of synthesis of IONPs [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56]Characterization of IONPs [57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected literature was classified into four main groups:Methods of synthesis of IONPs [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56]Characterization of IONPs [57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of IONPs [57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size dependence of the catalytic activity of ferrite nanoparticles was further studied by Liu and colleagues. They investigated the cytotoxic effects of small Fe 3 O 4 nanoparticles with different diameters (6, 9, and 14 nm) on human hepatoma cell lines, SK-Hep-1 and Hep3B (Xie et al, 2016 ). The 9 nm Fe 3 O 4 nanoparticles mediated mitochondria-dependent intracellular ROS generation to induce cellular mitochondrial dysfunction and necrosis, while the 14 nm Fe 3 O 4 nanoparticles led to plasma membrane damage.…”
Section: Ferrite-based Ros-mediated Cancer Therapymentioning
confidence: 99%
“…Polymers 2020, 12, x FOR PEER REVIEW 10 of 15 6 nm Fe3O4 NPs exhibited negligible cytotoxicity. However, Fe3O4 NPs with particle size larger than 9 nm may affect cytotoxicity by inducing cellular mitochondrial dysfunction or impairing the integrity of plasma membrane [41]. The particle size of the prepared Fe3O4 NPs is mainly concentrated between 4 and 6 nm, and this is the reason the Fe3O4 NPs prepared in this study showed no cytotoxic effects on cells.…”
Section: Cytotoxicity Characterization Resultsmentioning
confidence: 73%